QTL analysis uncovers the genetic architecture of resistance to chocolate spot disease caused by four Botrytis species on faba bean - Maniruzzaman,.; Jalli, Marja; Schulman, Alan H.; Khazaei, Hamid; Stoddard, Frederick L. (BioMed Central, 2026)
Background: Chocolate spot (CS), caused by Botrytis species, is a major disease constraining faba bean production worldwide. We investigated the genetic basis of resistance to four Botrytis species (B. fabae, B. cinerea, B. pseudocinerea, and B. fabiopsis) using a recombinant inbred line (RIL) population derived from the cross Mélodie/2 × ILB 938/2, which was evaluated with a detached-leaf assay. Results: Significant variation in disease severity was observed among parental lines and RILs for all four Botrytis species. The detached-leaf assay showed a strong correlation with a whole-plant assay conducted using a different B. fabae isolate, validating its effectiveness as a screening tool. QTL analysis identified six loci associated with response to Botrytis infection across Chr1, Chr4, and Chr6, explaining 7–11% of the total phenotypic variance. The overlapping QTLs on Chr1 conferred partial resistance to all four Botrytis species, while QTLs on Chr4 and Chr6 were specific to B. fabae. None of the other three species showed a unique QTL. Putative candidate gene analysis within QTL intervals revealed several defense-related gene families, including F-box protein, WRKY, MYB, and AP2/ERF transcription factors, and peroxidases involved in oxidative stress regulation. Conclusion: The consistency of response across species and the lack of unique responses from the non-fabae species suggests that selection for resistance to B. fabae may also select resistance to other Botrytis species. This study provides new insights into the shared and species-specific genetic architecture of Botrytis resistance in faba bean.
Keywords: gene mapping; quantitative trait loci; candidate gene; disease resistance; Botrytis spp.